Математична модель та оптимізаційне проектування торцевого електромеханічного перетворювача без механічних опор - Бова, Олександр (КІНПАТРІ ЛТД, 2013)
Design principles of design and creation of face induction motor, which has a secondary element serves as the rotor of the electric machine while performing useful mechanical work. This secondary element has no mechanical fastening, and kept in space and rotating by electromagnetic forces eliminates the mechanical link between the stator and the working body – rotor. In our case the rotor is free, ie no shaft and bearings.
Mathematical models and optimization design of face electromechanical transducer without mechanical resistance